Species identification in meat and cheese products by PCR-single strand conformation polymorphism (PCR-SSCP) and DNA sequencing - Csikós, Ádám; Tisza, Ákos; Simon, Ádám; Gulyás, Gabriella; Jávor, András; Czeglédi, Levente (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
In recent years species identification in foodstuffs by molecular biological methods have received more attention than in the earlier decades. The food adulteration scandals have highlighted to the importance of species identification techniques. In our study foodstuffs were analysed by PCR-SSCP and DNA sequencing techniques. Samples were originated from hypermarkets. DNA was extracted from foodstuffs. After DNA isolation we have amplified 278 bp region of 12S rRNA gene of mitochondrial genome. Amplified fragment was denaturated by high temperature and presence of formamide before SSCP. Denaturated PCR amplicons were separated by non-denaturing polyacrylamide gelelectrophoresis. DNA bands were visualized by silver-staining method. After PCR-SSCP analysis the non-denaturated PCR amplicons of 12 meat and 6 cheese products were analyzed by DNA sequencing. After PCR-SSCP analysis 6 meat products of 12 samples and 3 cheese products of 6 samples revealed to contain undeclared species. These results were confirmed by DNA sequencing that it showed the same results in the same samples. These results demonstrated that PCR-SSCP method is a reliable technique for species identification analysis in foodstuffs. Furthermore the PCRSSCP method is a low cost method compared to than DNA sequencing or real-time PCR techniques.